Molecular cloning, characterization, and expression of an alfalfa (Medicago sativa L.) heme oxygenase-1 gene, MsHO1, which is pro-oxidants-regulated - Fu, Guang-Qing (Plant physiology and biochemistry : PPB, 2011)
Copyright © 2011 Elsevier Masson SAS. All rights reserved.